2017
DOI: 10.1101/172338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical interneurons ensure maintenance of frequency tuning following adaptation

Abstract: Abstract.Neurons throughout the sensory pathway are tuned to specific aspects of stimuli. This selectivity is shaped by feedforward and recurrent excitatory-inhibitory interactions. In the auditory cortex (AC), two large classes of interneurons, parvalbumin-(PVs) and somatostatin-positive (SOMs) interneurons, differentially modulate frequency-dependent responses across the frequency response function of excitatory neurons. At the same time, the responsiveness of neurons in AC to sounds is dependent on the temp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The model accounted for observed experimental results including the differential role of SSTs and PVs in SSA [2], forward suppression [8], tuning-curve adaptation [7], and the effects of PV activation on feedforward functional connectivity [9]. We found that compensating currents between the two types of inhibitory neurons explain experimental findings of differential effects of their modulation on excitatory activity.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…The model accounted for observed experimental results including the differential role of SSTs and PVs in SSA [2], forward suppression [8], tuning-curve adaptation [7], and the effects of PV activation on feedforward functional connectivity [9]. We found that compensating currents between the two types of inhibitory neurons explain experimental findings of differential effects of their modulation on excitatory activity.…”
Section: Introductionmentioning
confidence: 73%
“…Specifically, SSTs, but not PVs facilitate stimulus-specific adaptation [2]. PVs and SSTs play distinct roles in adaptation to repeated tones along the frequency response function of the target neuron [7]. SSTs and PVs drive bi-directional effects on forward suppression [8].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations